Prediction of Meniscal and Ligamentous Injuries in Lateral Tibial Plateau Fractures Based on Measurements of Lateral Plateau Widening on Multidetector Computed Tomography Scans. (29th July 2018) - Kolb, Jan P.; Regier, Marc; Vettorazzi, Eik; Stiel, Norbert; Petersen, Jan P.; Behzadi, Cyrus; Rueger, Johannes M.; Spiro, Alexander S.
Abstract : Background . The influence of increasing lateral plateau widening on the frequency of meniscal and ligamentous lesions in lateral tibial plateau fractures has been examined in very few studies using plain radiographs. Because the amount of this parameter cannot be measured accurately on plain radiographs, the purpose of this survey was to look for a possible correlation between the extent of lateral plateau widening, as measured on multidetector CT (MDCT) scans, and different soft-tissue injuries determined from magnetic resonance imaging (MRI). Materials and Methods . 55 patients with a lateral tibial plateau fracture were included in this retrospective case series. Patient age averaged 52.6 years (SD = 18.0). The degree of lateral plateau widening was measured on CT images. MRIs were screened for meniscal and ligamentous injuries. Results . We found a significant effect of increasing lateral plateau widening on the incidence of lateral meniscus lesions (P = 0.021), lateral collateral ligament tears (P = 0.047), and the overall quantity of meniscal and ligamentous lesions (P = 0.001). Discussion . MRIs are not widely used as a diagnostic tool in lateral plateau fractures of the tibia. Reasons might be the costs and the fact that it is a time-consuming examination. The results of this study may help to estimate the probability of specific soft-tissue lesions in lateral tibial plateau fractures based on measurements of lateral plateau widening on MDCT scans, and they may guide the decision for additional MRI and/or arthroscopically assisted repair.